AN ANALYSIS OF TEACHER QUESTIONING DURING INTERACTION IN THE CLASSROOM - HASANATUN NISAK (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The current research is focused on analyzing the teacher's questions, what types of questions and asking techniques are used by the teacher in the classroom. For this type of question, the teacher uses the theory from Richards and Lockhart, while for the questioning technique uses the theory from Willen. This research uses descriptive qualitative research method. The data was obtained from the observation of the teacher's questions in the classroom, recording and interviews of the eighth grade English teacher at Ma'arif 03 Islamic Junior High School Malang. The results show that teacher tends to use convergent questions in the classroom. 24 convergent questions were used when asking students in class. The results also show 8 questioning techniques that teachers use when asking students in class. Asking questions clearly and concretely, asking questions according to the students ability level, asking questions logically and orderly, questions with insufficient levels, following up on students answers, and giving students time Think when answering, use questions that encourage broad student participation, and encourage students to ask questions.